(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
Annotation. The relevance of this study lies in the fact that today not only certain groups of users use cloud systems, but also many companies use them as a data warehouse and use them to exchange data. Cloud computing consists of such basic components as the platform core, interface, data storage, user management, application operation, which must monitor the system as a whole and ensure their protection. Accordingly, in this article, special attention has been paid to cloud computing and its various security approaches, as well as data encryption methods that perform encryption with symmetric and asymmetric keys. A cloud computing system can be exposed to various security threats, namely confidentiality, integrity, data availability and cloud infrastructure threats.